Can oil-led growth and structural change go hand in hand in Ghana? A multi-sector intertemporal general equilibrium assessment - Clemens Breisinger; Xinshen Diao; Manfred Wiebelt (Kiel Institute for the World Economy (IfW), 2012)
Unlike in Asia, the manufacturing sector has not (yet) become a driver of structural change in Africa. One common explanation is that the natural resource-focus of many African economies leads to Dutch disease effects. To test this argument for the case of newly found oil in Ghana we develop a multi-sector intertemporal general equilibrium model with endogenous savings and investment behavior. Results show that in addition to the well-known short-term Dutch disease effects, long-term structural effects can indeed impede Asian-style economic transformation in Ghana (and other resource rich countries). We also demonstrate how oil wealth may go hand in hand with structural change in the future.
Keywords: C68; D58; D90; F43; O11; O41; O55; 330; transformation; growth; structural change; oil revenue; Dutch disease; Ghana; intertemporal general equilibrium; Erdölvorkommen; Mineralölwirtschaft; Dutch Disease; Strukturwandel; Schätzung; Ghana